2021
DOI: 10.1002/jcp.30342
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise ameliorates cardiac hypertrophy by regulating mitochondrial quality control and endoplasmic reticulum stress through M2AChR

Abstract: Aerobic exercise increases M 2 AChR, which thus improves cardiac function in cardiovascular disease (CVD) rats. This study aimed to determine whether aerobic exercise could ameliorate pressure overload-induced heart hypertrophy through M 2 AChR, and to elucidate the underlying mechanisms of action. Mice were used to establish the myocardial hypertrophy model by transverse aortic constriction (TAC), and subjected to 2, 4, and 8 weeks of moderate-intensity aerobic exercise and choline intervention (14 mg/kg/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
3
19
0
2
Order By: Relevance
“…In addition, HIF1α in the myocardium of mice with both aetiologies of HF was also significantly reduced in the present study, which was consistent with the decreased HIF1α in the (Chang & Ma, 2017). Our findings confirmed that both MICT and HIIT improved autophagic flux and mitophagy levels in mice with ischaemic and pressure-overload HF, which was partially consistent with previous lesser evidence (Chang & Ma, 2017;Li et al, 2021;Ma et al, 2021;Moradi et al, 2019;Zhao et al, 2018).…”
Section: Exercises Differentially Facilitated Myocardial Mitophagysupporting
confidence: 93%
“…In addition, HIF1α in the myocardium of mice with both aetiologies of HF was also significantly reduced in the present study, which was consistent with the decreased HIF1α in the (Chang & Ma, 2017). Our findings confirmed that both MICT and HIIT improved autophagic flux and mitophagy levels in mice with ischaemic and pressure-overload HF, which was partially consistent with previous lesser evidence (Chang & Ma, 2017;Li et al, 2021;Ma et al, 2021;Moradi et al, 2019;Zhao et al, 2018).…”
Section: Exercises Differentially Facilitated Myocardial Mitophagysupporting
confidence: 93%
“…Interestingly, researchers have recently illustrated the relationship between aerobic exercise and hypertrophy, and they illustrated that in the mice persisting in aerobic exercise, cardiac hypertrophy and dysfunction were greatly improved. Mechanistically, mitochondria from the aerobic exercise group exhibited decreased excessive mitochondrial fission and mitochondrial autophagy, thus restoring mitochondrial ultrastructure and function in response to hypertrophic insults ( 81 ).…”
Section: Potential Therapeutic Approaches Targeting Mitochondria To Prevent or Reverse Cardiac Hypertrophymentioning
confidence: 99%
“…Overactivation of endoplasmic reticulum stress (ERS) and perturbation of mitochondrial function play a significant role in compensatory cardiac hypertrophy and progression to overt systolic heart failure ( Chaanine et al, 2013 ; Ma et al, 2021 ). Intraperitoneal injection of tunicamycin (TN) is an interesting model that can be used to study the functional effects of cardiac ER stress.…”
Section: The Critical Role Of Endoplasmic Reticulum-mitochondria Contacts In Remodeling and Cardiovascular Remodeling-associated Diseasesmentioning
confidence: 99%